Protective Effects of Four Structurally Distinct Sanshools Ameliorate Dextran Sodium Sulfate-Induced Ulcerative Colitis by Restoring Intestinal Barrier Function and Modulating the Gut Microbiota - Zhaojun Chen; Hui Wang; Lulin Tan; Xiong Liu (MDPI AG, 2024)
Hydroxy-α-sanshool (HAS), hydroxy-β-sanshool (HBS), hydroxy-γ-sanshool (HRS), and γ-sanshool (RS) are the key components from the Zanthoxylum genus, processing a range of pharmacological activities. The present study investigated the protective capacities of four sanshools on a dextran sulfate sodium (DSS)-induced model of ulcerative colitis (UC). The results showed that sanshool administration alleviated the colitis symptoms by reducing body weight loss and disease activity index (DAI) score, increasing the colon length, and improving colonic injury and the change in immune organ weight. Furthermore, sanshools enhanced the antioxidant enzyme activities, and RS exhibited the lowest effect on the improvement in total antioxidative capacity (T-AOC) and antioxidant abilities compared to the other three sanshools. The p65 nuclear factor κB (p65 NFκB) signaling pathway was inhibited to prevent hyperactivation and decreased the production of inflammatory factors. The gut barrier function in DSS-induced mice was restored by increasing goblet cell number and levels of tight junction proteins (zonula occludens-1, occludin, and claudin-1), and the levels of protein in HAS and HRS groups were higher than that in the HBS group, significantly. The analysis of gut microbiota suggested that sanshool administration significantly boosted the abundance of Lachnospiraceae, Muribaculaceae, Oscillospiraceae, and Alistipes and reduced the level of Buchnera in colitis mice. Collectively, the sanshool treatment could ameliorate colitis by resisting colon injury and regulating intestinal barrier dysfunction and gut microbiota dysbiosis; meanwhile, HRS and HAS have better improvement effects.